A Novel Diversity Receiver Design for Cooperative Transmission System - Jing Gao; Yinghui Zhang; Yang Liu (IEEE Access, 2018)
In this paper, we consider the performance of an amplify-and-forward relaying-based multiple-input multiple-output space-time-block-coded cooperative communication system. We propose an efficient two-stage receiver design for a relay-assisted transmission scenario over frequency-selective channels. It is also demonstrated that the receiver is able to achieve the full diversity order of the system by incorporating linear processing techniques. With this method, the potential spatial diversity and multipath diversity can be obtained by using the diversity-combining technique, which frequency-selective fading channels can be equivalently transformed. Simulation results show that the proposed scheme significantly outperforms the minimum mean square error and ZF receivers, while maintaining nearly linear complexity.